Advancing the utilization of 2D materials for electrocatalytic seawater splitting - Shemsu Ligani Fereja; Andleeb Mehmood; Qianqian Ji; Waseem Raza; Ahmed Hussen; Jie Hu; Shuo Zhai; Xingke Cai (InfoMat)
Abstract Applying catalysts for electrochemical energy conversion holds great promise for developing clean and sustainable energy sources. One of the main advantages of electrocatalysis is its ability to reduce conversion energy loss significantly. However, the wide application of electrocatalysts in these conversion processes has been hindered by poor catalytic performance and limited resources of catalyst materials. To overcome these challenges, researchers have turned to two‐dimensional (2D) materials, which possess large specific surface areas and can easily be engineered to have desirable electronic structures, making them promising candidates for high‐performance electrocatalysis in various reactions. This comprehensive review focuses on engineering novel 2D material‐based electrocatalysts and their application to seawater splitting. The review briefly introduces the mechanism of seawater splitting and the primary challenges of 2D materials. Then, we highlight the unique advantages and regulating strategies for seawater electrolysis based on recent advancements. We also review various 2D catalyst families for direct seawater splitting and delve into the physicochemical properties of these catalysts to provide valuable insights. Finally, we outline the vital future challenges and discuss the perspectives on seawater electrolysis. This review provides valuable insights for the rational design and development of cutting‐edge 2D material electrocatalysts for seawater‐electrolysis applications.